Collateral effects encountered by families of children living with physical or mental disabilities, or both, in Kilimanjaro, Tanzania: a cross-sectional study. (March 2018) - Joel, Caleb; Msuya, Sia; John, Beatrice; George, Johnston
Abstract: Background: Disability in low-income and middle-income countries (LMICs) is a neglected global health topic. Apart from the challenges faced by children living with disabilities, families of children living with disabilities are at increased risk of stress, weakened family and social relationships, reduced level of income, sense of depressed worthiness, decisions about whether to have more children, and reduced care to siblings without disabilities. This study focused on assessing collateral impacts on families of children younger than 18 years living with physical or metal disabilities, or both, in Kilimanjaro, Tanzania. Methods: This cross-sectional study was done between April and June, 2017. We used a household survey to assess families of children living with physical or mental disabilities, or both. Families were identified using convenience sampling, and data were analysed using SPSS version 23. Findings: 83 families from 33 villages in Kilimanjaro region were interviewed. 24 (29%) respondents reported weakened family relationships, the most profound effect being the father abandoning the mother and the child with disability (reported by nine [39%] respondents) and the least being misunderstanding between parents (reported by two [9%] respondents). 49 (59%) families reported having a decreased level of income, and 21 (25%) families mentioned reduced care to other siblings who have no disabilities. Furthermore, 20 (24%) families faced challenges in making decisions about whether to have more children, whereas 16 (19%) families felt a sense of worthlessness. Interpretation: Decreased income level and reduced care to other siblings have been associated with high costs of care, time, and resources spent taking care of the child with a disability. Adequate rehabilitation centres, special schools, and financial support for health-care accessibility could help reduce time and resources spent and hence potentiate productivity. Efforts should be focused on increasing the number of rehabilitation centres and special schools in the region, as Kilimanjaro has only one rehabilitation centre. Funding: None.